Posted by **a Canadian** on Friday, June 21, 2013 at 12:15am.

(delta)Eg = -14.7J

Therefore, Ek = -(delta)Eg = 14.7J

I don't understand how you'd come to the above conclusion? Does Ek just always equal -(delta)Eg?

## Answer this Question

## Related Questions

- Valid statements - Determine which statement follows validly from the statements...
- CHEMISTRY - Please explain. The enthalpy changes for two different hydrogenation...
- Chemistry - Please explain. The enthalpy changes for two different ...
- Chemistry(Please check answers) - 1) For a reaction delta Go is more negative ...
- Physics - 1. If the change in position delta(x) is related to velocity v (w/ ...
- physics - How can the alternative definition of power: P = \frac{w}{\Delta t} = ...
- Chemistry - 2M +6HCl–>2MCl+3H2 Delta H= -638.0 Kj HClg—>HCl aq= Delta H -...
- Chemistry - Clapeyron equation: dp/dT = ΔS / ΔV My textbook says, ...
- Calculus-Solved - Incorrect - calculate delta y for f(x)= x^(3/2) with x= 4 and ...
- Physics - I agree with this and see were it comes from net force = (delta p)/t ...

More Related Questions